Relationships of Spouses in Single-national and Inter-ethnic Russian, Tatar Families - Khusnutdinova, Rezida R.; Khakimova, Nailya G. (Journal of History Culture and Art Research, 2019)
This study is interested in the features of family relationship in mono and interethnic families as the factor defining the quality and the contents of real expectations and claims of spouses in spheres of family life. The relationships in the family depend mostly on traditions of communication, economic and social state of society, the participation of spouses in household activities. Moreover, it is necessary to consider the type of the family: families with many or no children, families with different leaders, personal qualities of relatives, and so on. The article is devoted to the study of family values in single-national and inter-ethnic Russian and Tatar families. Life of spouses can be examined under 5scalesphere: the sphere of professional life, the sphere of training and education, the sphere of family life, the sphere of social life and the sphere of hobbies. By implementing a fieldwork, this study demonstrated significant differences in views on family values in Russian, Tatar and mixed families. The investigation was conducted and completed and its results were analyzed and classified by the authors in accordance with the methods of the terminal values questionnaire of I.G. Senin and A.N. Volkova’s methodology "Role expectations and claims in marriage" which will be represented in detail below. The study involved 120 married couples of one-national and interethnic families of Russians and Tatars (240 people in total). The outcome of the study presented in the article is the description of cross cultural differences in family values, role expectations and claims of spouses in marriageon the basis of analyzing the indicators of coherence of family values in a Russian family. The materials of the article are of practical value for considering some features of the role structure of the modern family, and defining main directions in counseling married couples.